2007
DOI: 10.1248/bpb.30.1813
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Biofilms Produce More Secreted Aspartyl Protease than the Planktonic Cells

Abstract: By using a simple, low-cost system of polystyrene centrifuge tubes we compared the secreted aspartyl proteases (Saps) secretion during the biphasic growth modes of Candida albicans using twenty-one clinical isolates. Our results indicate that biofilms of C. albicans consistently secrete more Saps than their planktonic counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 10 publications
3
22
0
1
Order By: Relevance
“…In the present study, we also observed that T. inkin biofilms displayed more proteolytic activity than their planktonic counterparts. Similar results were found by Mendes et al (2007) in C. albicans biofilms. Taken together, these data suggest the importance of proteases in the development and maturation of T. inkin biofilms.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, we also observed that T. inkin biofilms displayed more proteolytic activity than their planktonic counterparts. Similar results were found by Mendes et al (2007) in C. albicans biofilms. Taken together, these data suggest the importance of proteases in the development and maturation of T. inkin biofilms.…”
supporting
confidence: 89%
“…The role of proteases in fungal biofilms has recently been studied in C. albicans. Secretory aspartic proteases genes are expressed in biofilm systems in vitro (Mendes et al, 2007;Nailis et al, 2010) and it has been hypothesized that these could be important for adhesion and nutrient acquisition in mature biofilms (Nailis et al, 2010). In the present study, we also observed that T. inkin biofilms displayed more proteolytic activity than their planktonic counterparts.…”
supporting
confidence: 72%
“…Mutant strains in which single SAP genes are deleted are viable, as are strains with deletions of multiple SAPs (69,149,186,334,375,403). The proteinase activity in biofilm culture supernatant is greater than that in planktonic organisms (241).…”
Section: Non-cell-wall Functionsmentioning
confidence: 99%
“…The main function of SAPs is to degrade proteins, but they also play a role in cell-cell adhesion [22]. [49] showed that C. albicans biofilms secrete more SAPs than do planktonic cells, while [50] showed that an in vitro C. albicans biofilm induced SAP activity, and that SAP8 expression within the biofilm correlated with in vivo denture stomatitis severity.…”
Section: Detection Of Als3 Sap5 Plb1 and Lip8 Genes In Candida Albimentioning
confidence: 99%